المسائل الفقهية المستنبطة من الحكم النبوية في العقوبات و الجھاد والقضاء: The Jurisprudential Issues Derived from The Prophetic Rulings in Punishments Jihad and Judiciary - Dr. Sumayyah Rafique; Muhammad Daud; Dr. Talib Ali Awan (AL-IDRAK JOURNAL, 2024)
This research aims to derive Islamic jurisprudential issues from the prophetic rulings related to three main areas: punishments, jihad, and judiciary. The Sunnah of the Prophet (PBUH) is the second source of Islamic legislation after the Qur’an. It encompasses wise directives and comprehensive rulings that regulate various aspects of life, including legal and judicial matters.In the area of punishments, the research discusses rulings related to hudud (fixed punishments), ta'zir (discretionary punishments), and qisas (retribution). It analyzes the legal objectives of these punishments, such as the protection of life, religion, honor, wealth, and intellect. The study also highlights the Prophet's (PBUH) wisdom in implementing punishments to achieve justice while considering the circumstances surrounding the crime and the offender.In the area of jihad, the research focuses on issues related to the conditions, etiquettes, and noble objectives of jihad, including promoting peace, protecting rights, and repelling aggression. The study examines the prophetic rulings concerning prisoners of war, the division of spoils, and treaties with non-Muslims, emphasizing the mercy and justice that characterized the Prophet's leadership.In the area of judiciary, the research explores the prophetic rulings related to the qualifications of a judge, their ethics, and judicial procedures. It also presents examples of cases adjudicated by the Prophet (PBUH), demonstrating his application of justice and equality among people without discrimination, as well as his keenness on reconciliation between disputants whenever possible.The study concludes that the prophetic rulings in these three areas are not merely legal texts but embody noble legal objectives aimed at achieving justice, mercy, and reform within society. These rulings also showcase the flexibility of Islamic legislation and its ability to adapt to various circumstances, making it a system suitable for all times and places.